The Royal Free Hospital 'hub-and-spoke network model' delivers effective care and increased access to liver transplantation. (January 2018) - Tai, D.; Dhar, A.; Yusuf, A.; Marshall, A.; O'Beirne, J.; Patch, D.; Tsochatzis, E.; Alexander, G.; Portal, J.; Thalheimer, U.; Thorburn, D.; Kallis, Y.; et al.
Abstract: Objectives: 'Hub-and-spoke' networks may be one solution to reduce the geographical inequality in access to liver transplantation (LT) and the growing demands on, and saturation of, LT centres. It is not clear if such networks improve equity of access, deliver comparable patient outcomes or effect patient satisfaction. Study design: Retrospective evaluation of outcomes and patient satisfaction within the Royal Free liver transplant 'hub-and-spoke' network. Methods: Patient outcomes in those assessed for LT between September 2011 and 2014 at spoke centres ( n = 4) were compared retrospectively with those assessed at the LT hub centre. Patient satisfaction questionnaires were completed and changes in LT referral patterns were explored with data obtained directly from NHS Blood and Transplant (NHSBT). Results: A total of 655 patients (180 spoke; 475 hub) were assessed for LT. Patients referred from spoke centres were more likely to have viral hepatitis as an underlying aetiology (72/180 vs 110/475; P < 0.001), or hepatocellular carcinoma (48/180 vs 60/475; P < 0.001) as an indication for LT and were more likely to be listed for LT when compared with hub patients (139/180 vs 312/475, P = 0.005). Mortality on the waiting list (9/123 vs 25/269, P = 0.57), waiting time to LT (64-days vs 78-days, P = 0.91) and Model for End-Stage liver disease (MELD)/United Kingdom End-Stage Liver Disease (UKELD) score ( P = 0.24/0.26) in listed patients were equivalent as were 1- and 3-year patient and graft survival rates. Patient satisfaction rates were high at both types of centre, with significantly more patients preferring 'locally delivered care' at spoke vs hub (11/50 vs 70/73, P ≤0.0001). Since the development of formal hub-and-spoke networks data from NHSBT based on postcode confirmed a significant increase in patients undergoing LT (153%) from spoke centres, whereas numbers assessed and transplanted from the hub centre have remained static. Conclusion: Hub-and-spoke LT networks are effective in offering equivalent clinical outcomes, high patient satisfaction and alleviate clinical pressure on the hub centre. They have to potential to help eliminate the geographical disparity in mortality rates from chronic liver disease. Highlights: There is significant geographical disparity in mortality from liver disease in the UK. Hub and spoke networks provide equivalent outcomes with respect to 1 and 3 year graft and patient survival. Hub and spoke LT care increases referrals and access to Liver transplantation. Patient satisfaction with 'locally delivered specialist care' is excellent. Hub and spoke care in Liver Transplantation may impact on the geographical imbalance.